Oil Price Risks and Pump Price Adjustments - Kojima, Masami (World Bank, Washington, DC, 2013)
Between 1999 and 2008, world oil prices more than quadrupled in real terms. For oil importers, vulnerability to oil price increases, defined as the share of gross domestic product spent on net oil imports, rose considerably. Considering medians, low-income countries had the highest vulnerability in 2008 and the highest increase in vulnerability between 1999 and 2008. When changes in vulnerability were decomposed into several contributing factors, more than two-thirds of 170 countries studied were found to have offset the increase in the value of oil consumption by reducing the oil intensity of gross domestic product. Oil intensity fell in more than half the countries in every income group and in every region of the world, driven by falling energy intensity and, to a lesser extent, the oil share of energy. This study also examines the degree of pass-through to consumers of increases in world prices of gasoline, diesel, kerosene, and liquefied petroleum gas between January 2009 and January 2012, when oil prices in nominal U.S. dollars more than doubled. Retail fuel prices varied by two orders of magnitude in 2012, and oil-exporting countries were far less likely to pass on price increases. Gasoline had the highest pass-through, followed by diesel, liquefied petroleum gas, and kerosene. The median pass-through increased with income for gasoline, diesel, and kerosene, but was highest in low-income countries for liquefied petroleum gas. Despite divergent pricing policies, the pass-through coefficients of different fuels were strongly positively correlated, suggesting that the degrees to which domestic prices tracked world prices were comparable for the four fuels in many countries.